The Importance of Renewing The Whistle Blower Regulation for Corruption Crimes in Indonesia - Patria, Vincentius (Universitas Proklamasi 45, 2024)
The existence of whistleblowers in disclosing corruption plays a very important role considering that corruption is carried out in a very neat and organized manner. Disclosure of corruption by a whistleblower certainly carries huge risks because the testimony given by the whistleblower is detrimental to the corruptor. The role of the whistleblower certainly needs to be provided with adequate legal protection. The purpose of writing this article is to analyze the concept of updating legal protection for whistleblowers in the future.This article was written using normative legal research methods with a statutory approach and a conceptual approach. The results of this research show that comprehensive protection is not only limited to legal protection and special protection that applies during the criminal justice process but also needs to be implemented after the criminal justice process has been completed, and it is necessary to reform institutional whistleblower protection.